Pengaruh Pelayanan Tenaga Administrasi Dan Kualitas Kerja Tenaga Medis Terhadap Kepuasan Pasien BPJS yang Dimoderasi oleh Kepercayaan Pasien - Lukiyana Lukiyana; Arsinta Arsinta (Universitas Bunda Mulia, 2018)
This study aims to analyze the effect of service quality on patient satisfaction BPJS users, analyze the service of administrative personnel to satisfaction, analyze the influence of the quality of medical workfor the user satisfaction BPJS.Kualitas service is a form of service provided by the service provider, in this case the hospital, with the quality of this service will impact on patient satisfaction. Research location at MH.Thamrin Hospital by taking samples of 100 patients using BPJS questionnaire. In this research using sampling technique using probabily sampling and data analysis method used in this research is PLS (Partial Least Square) 3.0. The result of this research is that the service of administration personnel is significant to the satisfaction of BPJS patient, the quality of the work of medical personnel is significant to the satisfaction of BPJS patient, the patient's trust is significant to the satisfaction of BPJS patient.Keywords: Customer Satisfaction, Trust, Work Quality